Opportunities to use building information modeling to improve Worker’s safety performance in construction projects in Libya - منذر البشير الخبي; رضا محمود الهوني (African Journal of Advanced Pure and Applied Sciences, 2025)
The study aimed to identify opportunities for using BIM to improve worker safety in construction projects in Libya, focusing on the extent to which construction companies and sectors are aware of the concept of BIM and the concept of safety and the extent to which they are applied by each construction company and sector. To achieve the study objective, the research investigated the relationship between BIM and safety to document opportunities, barriers and impacts using a descriptive analytical methodology and relied on questionnaires and an online survey of project engineers working in construction companies with a comprehensive review of the literature, where the number of participants in the questionnaire was 130 out of 150 questionnaires distributed, and the recovery rate was 86%. The data was analyzed using the SSPS statistical package. The study found that those who use BIM feel that it helps in communicating project information and delivering the project effectively, and has a positive impact on safety in addition to its positive impact on safety. In addition, according to the results of the questionnaire, a large percentage of engineers who use BIM feel that it ultimately helps in eliminating safety risks and improving worker safety. The results of the study indicate that improvements in safety performance may be due in part to the increased use of BIM in the construction industry. The results of this study also indicated the need for more practical BIM applications, with a particular focus on safety training and education, the use of BIM to enhance safety and resilience climates, and the development of quantitative risk analysis to better support safety management. Finally, the study recommends the use of BIM in all project phases and exploring ways to integrate BIM with advanced technologies and artificial intelligence.